Age-Related Alterations in Prelimbic Cortical Neuron Arc Expression Vary by Behavioral State and Cortical Layer - Hernandez, Abbi R.; Truckenbrod, Leah M.; Barrett, Maya E.; Lubke, Katelyn N.; Clark, Benjamin J.; Burke, Sara N. (Frontiers in Aging Neuroscience, 2020)
Prefrontal cortical and medial temporal lobe connectivity is critical for higher cognitive functions that decline in older adults. Likewise, these cortical areas are among the first to show anatomical, functional, and biochemical alterations in advanced age. The prelimbic subregion of the prefrontal cortex and the perirhinal cortex of the medial temporal lobe are densely reciprocally connected and well-characterized as undergoing age-related neurobiological changes that correlate with behavioral impairment. Despite this fact, it remains to be determined how changes within these brain regions manifest as alterations in their functional connectivity. In our previous work, we observed an increased probability of age-related dysfunction for perirhinal cortical neurons that projected to the prefrontal cortex in old rats compared to neurons that were not identified as projection neurons. The current study was designed to investigate the extent to which aged prelimbic cortical neurons also had altered patterns of Arc expression during behavior, and if this was more evident in those cells that had long-range projections to the perirhinal cortex. The expression patterns of the immediate-early gene Arc were quantified in behaviorally characterized rats that also received the retrograde tracer cholera toxin B (CTB) in the perirhinal cortex to identify projection neurons to this region. As in our previous work, the current study found that CTB+ cells were more active than those that did not have the tracer. Moreover, there were age-related reductions in prelimbic cortical neuron Arc expression that correlated with a reduced ability of aged rats to multitask. Unlike the perirhinal cortex, however, the age-related reduction in Arc expression was equally likely in CTB+ and CTB- negative cells. Thus, the selective vulnerability of neurons with long-range projections to dysfunction in old age may be a unique feature of the perirhinal cortex. Together, these observations identify a mechanism involving prelimbic-perirhinal cortical circuit disruption in cognitive aging.